Protest event dataset for Croatia, Portugal, Serbia and Spain : focus on strike data - Dolenec, Danijela (Array, 2021)
‘Disobedient Democracy: A Comparative Analysis of Contentious Politics in the European Semi-periphery’ is a research project implemented by the Faculty of Political Science of the University of Zagreb, in the period 2016-2021, led by Principal Investigator Danijela Dolenec and funded by the Swiss National Science Foundation (IZ11Z0_166540 – PROMYS). The overall objective of the project is to explore how protest politics advances democracy by collecting and analyzing data on protest mobilizations in four countries: Portugal, Spain, Croatia and Serbia.‎